The influence of granular and liquid top-dressed nitrogen on nitrogen use efficiency (NUE), grain yield and quality parameters of spring wheat (Triticum aestivum L.) - Mbangcolo, Mongezi Morrison (Stellenbosch : Stellenbosch University, 2018)
Thesis (PhD)--Stellenbosch University, 2018.